Cessation Attitudes and Preferences in Head and Neck Cancer Patients and Implications for Cessation Program Design: A Brief Report - Chandylen L Nightingale PhD, MPH; Katherine R Sterba PhD, MPH; Janet A Tooze PhD, MPH; Jessica L King PhD; Kathryn E Weaver PhD, MPH (SAGE Publishing, 2019)
Introduction This brief report examined prior cessation attempts, attitudes toward nicotine replacement therapy (NRT), and interests in cessation interventions among head and neck cancer (HNC) patients with a recent smoking history (current smokers and recent quitters). Methods Forty-two HNC patients scheduled for major surgery who reported current or recent (quit <6 months) cigarette smoking participated. Participants completed a survey to assess smoking status, prior cessation attempts, attitudes toward NRT, and interest in and preferences for cessation interventions. Results Patients attempted to quit smoking on average 3.2 times in the past 12 months. Most patients (65.8%) reported that NRT products help people quit, with 42.5% reporting ever using cessation aids/services. Most patients (81.8%) reported interest in a smoking cessation program. Current smokers and recent quitters reported similar cessation attempts, attitudes toward NRT, and interest in smoking cessation interventions. Discussion Cancer center-based smoking cessation interventions are needed for current smokers and recent quitters maintaining cessation.